Konsep al-Illah wa al-Ma'lul Ikhwan al-Safa': Satu Analisa Risalah Fi al-'Ilal wa Al-Ma'lulat - Wan Abdullah, Wan Suhaimi (Jurnal Usuluddin, 1995)
The Brethren of Purity (Ikwan Al-Safa wa Khullan Al-Wafa) is the most popular movement in Islamic cosmology. This movement has their own encyclopaedia of science which is known as Rasail Ikhwan al-Safa. This encyclopaedia is a unique encyclopaedia which contains 52 "maqalah" and divided into 4 categories in various knowledge, i.e. mathematic and education, natural science, rational science and physiological science and theological science. In rational science and psychological science there is an article in 9 (risalah) which is the study about cause and effect. The study of cause and effect is mentioned in both rational and phsycological sciences. This study according to Ikhwan al-Safa is rather difficult but interesting. Certain criteria are needed particularly in the study of cause and effect, i.e. detail study, good attitude and moral, cleanliness spiritual, high knowledge and perfect understand and using the right methodology. Ikhwan al-Safa has divided the study of cause into 4 categories, i.e. "maker", "jirim", "figure" and "vision" whereas the study of effect is divided into 4 categories, i.e. "human creation", "nature", "spiritual" and "al-ruhaniyyat al-llahiyyat". Therefore this article attempts to elaborate the study of cause and effect according to Rasail al-Safa.